Aplikasi E-Commerce Galeri Lembaga Adat Melayu Riau Berbasis Mobile Menggunakan Flutter Menerapkan Metode Waterfall - Andrian Wahyu; Muhammad Affandes; Pizaini Pizaini; Yelfi Vitriani; Iwan Iskandar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The Galeri LAM Riau is an effort by the Riau Malay creative and cultural economic center to showcase products typical of the Riau region which include culinary, souvenirs, clothing and handicrafts typical of Riau. The Galeri LAM Riau is fostered by PT Pertamina Hulu Rokan to advance regional MSMEs products and find out what traditions exist in Riau. Seeing the business processes carried out by the Galeri LAM Riau, there are still many buying and selling activities carried out that have not utilized technological developments and the concept of e-commerce. The process of buying and selling transactions in e-commerce is quite important because in the current era of globalization it greatly facilitates many jobs and helps many parties. The flutter e-commerce application of the Galeri LAM Riau can be a solution for producing product output that can help process buying and selling transactions at the Galeri LAM Riau by designing the waterfall method. This waterfall method has a fairly clear work flow, measurable work time and clear documentation. With these advantages, the costs incurred are well detailed and save expenses. The application will also carry out the black box testing to valid stage to ensure smooth transactions before the application is used. The results of this study are 3 types of applications that can be used properly based on their respective authorities according to the features needed. This research is expected the app help facilitate transactions, services, reports and available information at the Galeri LAM Riau.